Numerical Studied for Solving Fuzzy Integro-Differential Equations via Caputo Fractional Derivative - Ruaa N. Abduallah; Rokan khaji (Academic Science Journal)
In this paper, we extended some numerical methods to solve fuzzy integro differential equations. The considered problem involves the fractional Caputo derivatives under some conditions on the ordered. As we combine Euler's method with composite Simpsons have been used to determine the solutions of these equations. We extend these numerical techniques to find the best solutions. Extended difference Euler technique is used for this. The results show that the extended Euler method is more accurate in terms of absolute error. Illustrative examples are given to demonstrate the high precision and good performance of the new class.